Ultrathin Two-Dimensional Inorganic Materials: New Opportunities for Solid State Nanochemistry - Sun, Yongfu; Gao, Shan; Lei, Fengcai; Xiao, Chong; Xie, Yi (Accounts of chemical research, 2015)
The ultimate goal of solid state chemistry is to gain a clear correlation between atomic, defect, and electronic structure and intrinsic properties of solid state materials. Solid materials can generally be classified as amorphous, quasicrystalline, and crystalline based on their atomic arrangement, in which crystalline materials can be further divided into single crystals, microcrystals, and nanocrystals. Conventional solid state chemistry mainly focuses on studying single crystals and microcrystals, while recently nanocrystals have become a hot research topic in the field of solid state chemistry. As more and more nanocrystalline materials have been artificially fabricated, the solid state chemistry for studying those nanosolids has become a new subdiscipline: solid state nanochemistry. However, solid state nanochemistry, usually called “nanochemistry” for short, primarily studies the microstructures and macroscopic properties of a nanomaterial’s aggregation states. Due to abundant microstructures in the aggregation states, it is only possible to build a simple but imprecise correlation between the microscopic morphology and the macroscopic properties of the nanostructures. Notably, atomically thin two-dimensional inorganic materials provide an ideal platform to establish clear structure–property relationships in the field of solid state nanochemistry, thanks to their homogeneous dispersion without the assistance of a capping ligand. In addition, their atomic structures including coordination number, bond length, and disorder degree of the examined atoms can be clearly disclosed by X-ray absorption fine structure spectroscopy. Also, their more exposed interior atoms would inevitably induce the formation of various defects, which would have a non-negligible effect on their physicochemical properties. Based on the obtained atomic and defect structural characteristics, density-functional calculations are performed to study their electronic structures. Then, after the properties of the individual ultrathin two-dimensional materials or their assembled highly oriented thin film-based nanodevices are measured, the explicit relationship between atomic, defect, and electronic structure and intrinsic properties could be established. In this Account, we focus on our recent advances in the field of solid state nanochemistry, including atomic structure characterization of ultrathin two-dimensional inorganic materials by X-ray absorption fine structure spectroscopy, characterization of their different types of structural defects by positron annihilation spectra and electron spin resonance, and investigation of their electronic structure by density-functional calculations. In addition, we summarize the close correlation between atomic, defect, and electronic structure variations and the optoelectronic, electrical, magnetic, and thermal properties of ultrathin two-dimensional materials. Finally, we also propose the major challenges and opportunities that face solid state nanochemistry. We believe that all the past achievements in ultrathin two-dimensional materials could bring new opportunities for solid state nanochemistry.